Phylogeny determines flower size-dependent sex allocation at flowering in a hermaphroditic family - Teixido, A. L.; Guzmán, B.; Staggemeier, V. G. [UNESP]; Valladares, F. (Wiley, 2017)
In animal-pollinated hermaphroditic plants, optimal floral allocation determines relative investment into sexes, which is ultimately dependent on flower size. Larger flowers disproportionally increase maleness whereas smaller and less rewarding flowers favour female function. Although floral traits are considered strongly conserved, phylogenetic relationships in the interspecific patterns of resource allocation to floral sex remain overlooked. We investigated these patterns in Cistaceae, a hermaphroditic family. We reconstructed phylogenetic relationships among Cistaceae species and quantified phylogenetic signal for flower size, dry mass and nutrient allocation to floral structures in 23 Mediterranean species using Blomberg's K-statistic. Lastly, phylogenetically-controlled correlational and regression analyses were applied to examine flower size-based allometry in resource allocation to floral structures. Sepals received the highest dry mass allocation, followed by petals, whereas sexual structures increased nutrient allocation. Flower size and resource allocation to floral structures, except for carpels, showed a strong phylogenetic signal. Larger-flowered species allometrically allocated more resources to maleness, by increasing allocation to corollas and stamens. Our results suggest a major role of phylogeny in determining interspecific changes in flower size and subsequent floral sex allocation. This implies that flower size balances the male–female function over the evolutionary history of Cistaceae. While allometric resource investment in maleness is inherited across species diversification, allocation to the female function seems a labile trait that varies among closely related species that have diversified into different ecological niches.
Keywords: Allometry; Cistaceae; dry mass; female function; male function; nutrients; phylogenetic signal